REINTERPRETATION OF THE HADITH ON RECYCLED WATER WITH A SCIENTIFIC APPROACH - Syukron, Tubagus Muhammad; Fudhaili, Ahmad (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2024)
The hadith concerning the well of Budhāʻah, known for its contaminated condition, raises intriguing questions regarding Prophet Muhammad’s use of its water for ablution. The contradiction between the well’s description and the prophet’s action has prompted scholarly interpretations about a possible natural purification process. However, existing explanations regarding this purification do not fully align with the well’s condition as described in the hadith. This study reinterprets the Budhāʻah well hadith to determine the legal status of recycled water using modern scientific findings. Collaborating with PT Rofis Jaya Perkasa, a wastewater treatment company, this research aims to scientifically reconstruct the well’s historical condition. Employing a qualitative approach with a case study on the Budhāʻah well hadith, this research gathers data through literature review, interviews, and field observations. Hadith analysis involves scrutiny of its chain of sanad, matan, and contextual understanding using scientific theories. The analysis reveals that the well’s water was a mixture of rainwater and periodically entering household wastewater. Natural mechanisms, including microbial activity, were capable of transforming the contaminated water into cleaner water. These findings offer a new perspective on the concept of water purity in Islam, particularly concerning recycled water and its relevance to modern water treatment practices. [Hadis tentang Sumur Budhāʻah, yang dikenal karena kondisinya yang tercemar, menimbulkan pertanyaan menarik terkait penggunaan airnya oleh Nabi Muhammad untuk berwudu. Kontradiksi antara deskripsi sumur dan tindakan Nabi memunculkan interpretasi ulama tentang kemungkinan adanya proses semacam daur ulang. Kendati demikian, penjelasan mengenai proses penyucian air ini tidak sesuai dengan kondisi Sumur Budhāʻah sebagaimana yang termaktub dalam hadis. Penelitian ini akan menginterpretasi ulang hadis Sumur Budhāʻah dalam menentukan status hukum air daur ulang menggunakan pendekatan temuan sains modern. Melalui kolaborasi dengan PT Rofis Jaya Perkasa, sebuah perusahaan yang bergerak di bidang pengolahan air limbah, penelitian ini berusaha merekonstruksi secara ilmiah kondisi Sumur Budhāʻah pada masa lalu. Penelitian ini menggunakan pendekatan kualitatif dengan studi kasus pada hadis Sumur Budhā‘ah. Metode pengumpulan data meliputi studi pustaka, wawancara, dan observasi lapangan. Hadis akan ditinjau menggunakan kritik sanad, kritik matan, dan pemahaman hadis kontekstual dengan pendekatan teori sains. Hasil analisis menunjukkan bahwa air di Sumur Budhāʻah merupakan campuran air hujan dan limbah rumah tangga yang masuk berkala. Mekanisme alami, termasuk aktivitas mikroorganisme, mampu mengubah kualitas air yang tercemar menjadi air yang lebih bersih. Temuan ini membuka perspektif baru dalam memahami konsep kesucian air dalam Islam, khususnya terkait dengan air hasil daur ulang.]